(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3eMeO HfYaQ GdhQcGfj , MOKfG MOjL CHh SdjeGf , Yf CHj ESMGb , Yf eWQ Hf YcGeS , bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3dG jbOQ dCMO jehJ HCQV , EdG MHHJ Edjg hLYd dg EdjgG MGLI MOjK ejehf Hf SfHGPs
(3BNQgG (B:s
(3KfG jMji Hf SYjO , KfG YHO GdLdjd bGd (B: (3GfJgjJ Edi MdbI ajgG CHh eLdR , h GHf HQjOI abGd (B: (3YHO Gddg Hf HQjOI , MOKfj CHj HQjOI bGd (B: (3CHZVJ YdjG HZVG de CHZVg CMO (B( (3cPG (B) (3bW bGd (B: (3hCMHHJ QLdG ef bQjT de CMHg EdG Ydi HZVg YdjG bGd (B: (3aHYK Pdc GdQLds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs